Concurrent chemoradiotherapy with S-1 versus platinum in the treatment of locoregionally advanced nasopharyngeal carcinoma: a multicenter, retrospective, propensity score-matched analysis - Bian, Chenbin; Zheng, Zhuangzhuang; Su, Jing; Chang, Sitong; Yu, Huiyuan; Bao, Jindian; Zhao, Qin; Jiang, Xin (Frontiers in Pharmacology, 2024)
Literature data are scarce on concurrent chemoradiotherapy (CCRT) with S-1 for locally advanced nasopharyngeal carcinoma (LANPC) treatment. This study compared the efficacy and safety of the S-1 versus platinum-based CCRT in LANPC treatment.This study enrolled 547 patients newly diagnosed with LANPC who underwent CCRT with S-1 or platinum at three institutions. Propensity score matching in a 1:1 ratio balancing baseline features was performed. Survival and adverse effects were compared between groups.Of 160 patients in the cohort, 100 eligible were propensity score matched. Matched dataset analyses showed a higher 5-year overall survival rate (87.1% vs. 84.7%, P = 0.833), progression-free survival (79.6% vs. 75.5%, P = 0.669), locoregional recurrence-free survival (87.0% vs. 84.7%, P = 0.518), and distant metastasis-free survival (84.8% vs. 83.0%, P = 0.780) in the S-1 group than in the platinum-based CCRT group, although not statistically significant. Objective response rate (98.0% vs. 88.0%, P = 0.117) was significantly higher in the S-1 than in the platinum-based regimen, although it was not statistically reflected. Compared with platinum-based, those undergoing S-1-based chemotherapy demonstrated a higher incidence of grade 3 mucositis (20.0% vs. 2.0%, P = 0.016) in the S-1 group and a lower incidence of leukopenia (44.0% vs. 68.0%, P = 0.033), neutropenia (28.0% vs. 52.0%, P = 0.032), anemia (22.0% vs. 44.0%, P = 0.040), nephrotoxicity (4.0% vs. 20.0%, P = 0.028), and nausea/vomiting (30.0% vs. 56.0%, P = 0.019).The results suggest that S-1 can be used as a concurrent chemotherapy regimen during radiotherapy for patients with LANPC, since it presents a noninferior survival benefit compared with platinum and shows tolerable adverse effects.